Prime Minister Decree 1806/2016 On Amending Certain Provisions Of The Executive Regulations Of Law No 156/2002 On Establishing Emergency Relief Fund For Workers = قرار رئيس مجلس الوزراء رقم 1806 لسنة 2016 بتعديل بعض أحكام اللائحة التنفيذية للقانون رقم 156 لسنة 2002 بإنشاء صندوق إعانات الطواريء للعمال الصادرة بقرار رئيس مجلس الوزراء رقم 1395 لسنة 2002 - Egypt; The middle east library for economic services, translator. (2025)
Prime minister decree no. 1806 of the year 2016 قرار رئيس مجلس الوزراء رقم 1806 لسنة 2016